Model Law on Access to Information for Africa and other regional instruments: Soft law and human rights in Africa - Ololade Shyllon (Pretoria University Law Press (PULP), 2018)
The adoption in 2013 of the Model Law on Access to Information for Africa by the African Commission on Human and Peoples' Rights is an important landmark in the increasing elaboration of human rights-related soft law standards in Africa. Although non-binding, the Model Law significantly influenced the access to information landscape on the continent. Since the adoption of the Model Law, the Commission adopted several General Comments. The AU similarly adopted Model Laws such as the African Union Model Law on Internally Displaced Persons in Addressing Internal Displacement in Africa. This collection of essays inquires into the role and impact of soft law standards within the African human rights system and the AU generally. It assesses the extent to which these standards induced compliance, and identifies factors that contribute to generating such compliance. This book is a collection of papers presented at a conference organised by the Centre for Human Rights, University of Pretoria, with the financial support of the government of Norway, through the Royal Norwegian Embassy in Pretoria. Following the conference, the papers were reviewed and reworked.